2019
DOI: 10.3906/biy-1908-10
|View full text |Cite
|
Sign up to set email alerts
|

In vitro study on chondrogenic differentiation of human adipose-derived stem cells on treated bovine pericardium

Abstract: Bovine pericardium has been proposed as an available material for tissue engineering and bioprosthetic reconstruction. In this study, bovine pericardium was fabricated into a scaffold for culturing and chondrogenic differentiation of human adipose-derived stem cells (hADSCs). Bovine pericardium was treated in 10 mM Tris-HCl and 0.15% SDS, followed by crosslinking in 0.1% glutaraldehyde. Treated bovine pericardium (tBP) was characterized as a slight yellowish thin membrane with enhanced tensile strength and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
(35 reference statements)
0
1
0
1
Order By: Relevance
“…Moreover, many researchers have successfully induced chondrogenic differentiation of ADSCs in vitro and in vivo (Goudarzi et al, 2018;Hwang, Noh, Hong, & Lee, 2020;Yang, Chen, Yang, Hsiao, & Wang, 2020). And in the field of cartilage tissue engineering, an increasing number of studies have confirmed that adipose stem cells have good chondrogenic differentiation ability, which is comparable to bone marrow stromal stem cells (Chung et al, 2019;Keshavarz, Jalili, Pazhouhi, & Khazaei, 2019;Nguyen, Doan, & Tran, 2019). Therefore, ADSCs are cartilage tissue engineering seed cells, with rare advantages and prospects.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many researchers have successfully induced chondrogenic differentiation of ADSCs in vitro and in vivo (Goudarzi et al, 2018;Hwang, Noh, Hong, & Lee, 2020;Yang, Chen, Yang, Hsiao, & Wang, 2020). And in the field of cartilage tissue engineering, an increasing number of studies have confirmed that adipose stem cells have good chondrogenic differentiation ability, which is comparable to bone marrow stromal stem cells (Chung et al, 2019;Keshavarz, Jalili, Pazhouhi, & Khazaei, 2019;Nguyen, Doan, & Tran, 2019). Therefore, ADSCs are cartilage tissue engineering seed cells, with rare advantages and prospects.…”
Section: Discussionmentioning
confidence: 99%
“…Màng được tạo ra bằng cách loại bỏ hoàn toàn thành phần tế bào trong màng tim heo bằng phương pháp khử tế bào. Màng tim khử tế bào (dPP) được chứng minh là có cấu trúc collagen đặc, tính tương hợp sinh học, không gây độc cho tế bào, khả năng hỗ trợ tế bào tăng sinh tốt [10], [9]. Ngoài ra, việc sản xuất màng dPP hoàn toàn có thể tiến hành ở quy mô công nghiệp với giá thành rẻ vì đây làm sản phẩm thải trong chăn nuôi heo.…”
Section: đặT Vấn đềunclassified